Покращення показників експлуатації маневрово-вивозних тепловозів депо З - Недільський, Юрій Мар'янович; Nedilskyi, Yurii Marianovych (Національний університет "Львівська політехніка", 2024)
Метою даної бакалаврської роботи є підвищення ефективності роботи локомотивів, що задіяні у маневрово-вивізній роботі. Об’єктом дослідження є система технічної експлуатації маневрововивозних локомотивів. Предметом дослідження є показники експлуатації маневрово-вивозних локомотивів. У бакалаврській роботі запропоновано заходи з підвищення ефективності використання локомотивів, що задіяні у маневрово-вивізній роботі з врахуванням специфіки цієї роботи. Для досягнення цієї мети у роботі проаналізовано особливості виконання маневрово-вивізних робіт, техніко-економічні параметри локомотивів, що задіяні у їх виконанні, систему кількісних та якісних показників використання даних локомотивів. Встановлено, що існуюча система обліку кількісних та якісних показників не у повній мірі підходить до аналізу роботи маневрово-вивізних локомотивів. У зв’язку з цим запропоновано новий перелік показників та засоби їх обліку. Запропоновано шляхи покращення удосконалених показників використання. У відповідному розділі розглянуто питання охорони праці і запропоновано заходи з покращення.

The aim of this bachelor’s thesis is to improve the operational efficiency of locomotives involved in shunting and transfer operations. The object of the study is the system of technical operation of shunting and transfer locomotives. The subject of the study is the operational performance indicators of shunting and transfer locomotives. This bachelor’s thesis proposes measures to increase the efficiency of locomotive utilization in shunting and transfer operations, taking into account the specific features of such activities. To achieve this aim, the thesis analyses the characteristics of shunting and transfer operations, the technical and economic parameters of the locomotives involved, and the system of quantitative and qualitative indicators used to evaluate their performance. It was established that the existing system for recording quantitative and qualitative indicators does not fully suit the needs of analysing the operation of shunting and transfer locomotives. Therefore, a new set of performance indicators and methods for recording them has been proposed. Additionally, ways to improve these enhanced indicators of locomotive utilization are presented. A separate section of the thesis is devoted to occupational health and safety issues, along with proposed measures for improvement in this area.
Enhancement of the Operational Performance of Shunting and Transfer Diesel Locomotives at Depot Z
Keywords: 6.273.00.02; локомотивне депо; маневрово-вивізна робота; показники використання; тепловоз; удосконалення; locomotive depot; shunting and transfer operations; utilization indicators; diesel locomotive; improvement